Vibration energy harvesting using piezoelectric transducer and non-controlled rectifiers circuits - Motter, Daniel; Lavarda, Jairo Vinicius; Dias, Felipe Aguiar; da Silva, Samuel [UNESP] (Abcm Brazilian Soc Mechanical Sciences & Engineering, 2012)
Vibration energy harvesting with piezoelectric materials is of practical interest because of the demand for wireless sensing devices and low-power portable electronics without external power supply. For practical use of vibration energy harvester with piezoelectric materials, it is necessary to process the alternating current (AC) by using different rectifiers' circuits in order to charge batteries with direct current (DC) or to feed electronic devices. Unfortunately, most of the models used focused on simplifying the energy harvesting circuit into a simple resistive load. In the real-world applications, the energy harvesting external circuit is more complex than a simple load resistance. In this sense, the goal of the present paper is to describe a comprehensive strategy for power harvesting device to estimate the output power provided by a cantilever beam with the electrodes of the piezoceramic layers connected to a standard rectifier circuit. The true electrical components were considered in the full-wave rectifier circuit with four diodes in bridge. A very simple and comprehensive description for choosing the capacitance and resistance loads is provided. In order to illustrate the results, numerical simulations and experimental verifications are also performed to ensure the accuracy. All tests and results are described and detailed using Matlab, the SimPowerSystem toolbox of the Simulink and an experimental setup.
Keywords: smart structures; piezoelectric transducers; energy harvesting; rectifier circuit